Reactive oxygen and nitrogen species in normal physiological processes - Pourova, J; Kottova, M; Voprsalova, M; Pour, M (Acta physiologica (Oxford, England), 2010)
Abstract Reactive oxygen species (ROS) and reactive nitrogen species have generally been considered as being highly reactive and cytotoxic molecules. Besides their noxious effects, ROS participate in physiological processes in a carefully regulated manner. By way of example, microbicidal ROS are produced in professional phagocytes, ROS function as short-lived messengers having a role in signal transduction and, among other processes, participate in the synthesis of the iodothyronine hormones, reproduction, apoptosis and necrosis. Because of their ability to mediate a crosstalk between key molecules, their role might be dual (at least in some cases). The levels of ROS increase from a certain age, being associated with various diseases typical of senescence. The aim of this review is to summarize the recent findings on the physiological role of ROS. Other issues addressed are an increase in ROS levels during ageing, and the possibility of the physiological nature of this process.
Keywords: reaktivní formy dusíku; Reactive Oxygen Species; signální transdukce; Signal Transduction; Reactive Nitrogen Species; zvířata; Humans; lidé; reaktivní formy kyslíku; Animals